Perancangan Busana Magnificent Of Modular Mode - Meilinda Lenawati; Rachmawaty - (Institut Seni Indonesia Padangpanjang, 2021)
Fast fashion can be interpreted as a quick response effort in providing the latest fashionable clothes according to consumer demand. This can lead to a accumulation of clothes which eventually becomes clothing waste. Clothing waste can be overcome with two opportunities, namely reuse and reduction, this reduction method uses the principle of sustainable design. Sustainable that is raised is a modular design.